SPE Annual Technical Conference and Exhibition 1997
DOI: 10.2118/38573-ms
|View full text |Cite
|
Sign up to set email alerts
|

Microseismic and Deformation Imaging of Hydraulic Fracture Growth and Geometry in the C Sand Interval, GRI/DOE M-Site Project

Abstract: Six hydraulic-fracture injections into a fluvial sandstone at a depth of 4300 ft were monitored with multi-level tri-axial seismic receivers in two wells and an inclinometer array in one well, resulting in maps of the growth and fmal geometry of each fracture injection. These diagnostic images show the progression of height and length growth with fluid volume, rate and viscosity. Complexities associated with shut downs and high treatment pressures can be observed. Validation of the seismic geometry was made wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(16 citation statements)
references
References 0 publications
0
16
0
Order By: Relevance
“…Ongoing evaluation of this configuration entails adding noise to the arrival time picks, and incorporating S-waves and inaccurate velocity models into the search procedure. Warpinski et al (1997) clearly demonstrate the utility of microseismic event location for mapping hydraulically induced fractures within a fluvial sand-shale petroleum reservoir. Figures 2 -4 display 20 event positions obtained by inverting P-wave and S-wave arrival times observed by an array of cemented, triaxial accelerometers deployed in a single monitor well.…”
Section: Synthetic Data Examplementioning
confidence: 69%
“…Ongoing evaluation of this configuration entails adding noise to the arrival time picks, and incorporating S-waves and inaccurate velocity models into the search procedure. Warpinski et al (1997) clearly demonstrate the utility of microseismic event location for mapping hydraulically induced fractures within a fluvial sand-shale petroleum reservoir. Figures 2 -4 display 20 event positions obtained by inverting P-wave and S-wave arrival times observed by an array of cemented, triaxial accelerometers deployed in a single monitor well.…”
Section: Synthetic Data Examplementioning
confidence: 69%
“…Tensile opening can be a physical process following fluid injection and hydraulic fracturing operations. Although in some cases, no evidence for tensile source radiation patterns was found (Nolen-Hoeksema & Ruff, 2001;Phillips, Fairbanks, Rutledge, & Anderson, 1998;Warpinski, 1997), later studies identified significant non-DC terms for hydrofracture events (Jechumt alov a & Eisner 2008; Sileny et al, 2009;Warpinski & Du, 2010). Similar non-DC source models have also been proposed for induced seismicity in geothermal environments (Zhao, K€ uhn, Oye, & Cesca, 2014).…”
Section: The Microseismic Sourcementioning
confidence: 85%
“…The depth distribution of microearthquakes presented by Rutledge and Phillips (2003) is generally contained in intervals with heights of less than 10 m around approximately 5-m perforation zones. Closer to the Rulison site, a series of six hydrofracture operations in the 15-m-thick B-Sand of the lower fluvial interval of the Williams Fork at the MWX site produced a range of fracture heights from 12 to 41 m, with an average of 22.4 m. Warpinski et al (1997) similarly found that hydrofractures were generally contained within the C-sand during injections in that unit.…”
Section: Vertical Extent Of Hydraulic Fracturesmentioning
confidence: 86%
“…Most estimates are the result of interpretation of microseismic signals. Warpinski et al (1997) used a variety of data, including intersecting wells, to demonstrate that microseismic activity can provide a reliable image of a hydraulic fracture. The ideal hydraulic fracture is usually considered a single feature spreading from the stimulated well (a "bi-wing" fracture).…”
Section: Hydraulic Fracture Zone Geometrymentioning
confidence: 99%